2016
DOI: 10.1590/0103-6440201600569
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of a Bisphenol-A-Free Fissure Sealant With and Without Adhesive Layer under Conditions of Saliva Contamination

Abstract: Dental sealants are important for prevention of carious lesions, if they have good shear strength. The aim of this study was to evaluate the shear bond strength (SBS) of two sealants to saliva-contaminated and non-contaminated enamel with and without an intermediate adhesive layer underneath the sealant. Ninety flat enamel surfaces from human third molars were randomly assigned to 6 groups (n=15): F (control): Fluroshield™ sealant; EWB (control): Embrace™ WetBond™; SB/F: Single Bond adhesive system + F; SB/ EW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
(33 reference statements)
1
11
0
2
Order By: Relevance
“…Similar to these studies, the results of the present study also showed a significant difference between bonding and non-bonding groups, and a higher percentage of microleakage in non-bonding groups. These findings are in line with the results of the studies carried out by Bahrololumi et al [12] and Mesquita-Guimarães et al [18]. Cehreli and Gungor [14] evaluated the microleakage of Helioseal F fissure sealant with and without different bonding agents.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Similar to these studies, the results of the present study also showed a significant difference between bonding and non-bonding groups, and a higher percentage of microleakage in non-bonding groups. These findings are in line with the results of the studies carried out by Bahrololumi et al [12] and Mesquita-Guimarães et al [18]. Cehreli and Gungor [14] evaluated the microleakage of Helioseal F fissure sealant with and without different bonding agents.…”
supporting
confidence: 89%
“…Hence, bonding systems were recommended to be used before sealant to reduce the effects of saliva contamination. Mesquita-Guimarães et al [18] evaluated the effect of saliva contamination on bond strength of a Bisphenol-A free fissure sealant with and without an adhesive layer. They concluded that an adhesive system layer should be used prior to the sealant placement in either dry and saliva-contaminated enamel.…”
mentioning
confidence: 99%
“…However, other studies found that the addition of this step had no advantages ( 6 , 7 ). One study reported that applying an adhesive reduced the negative effect of saliva contamination on sealant bond strength to the enamel surface ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mesquita-Guimarães et al in 2016 evaluated the shear bond strength of hydrophilic resinbased fissure sealant on 90 extracted third molars teeth in a laboratory study using saliva contaminated and non-contaminated surfaces. Embrace WetBond exhibited the lowest shear bond results as reported in comparison to Fluoroshield hydrophobic sealant (27).…”
Section: Introductionmentioning
confidence: 77%
“…The bond strength was calculated according to following equation: Shear bond strength (MPa) = the maximum failure load recorded in (N)/surface area in mm2 Finally Fracture mode assessment (27) was completed by examining each specimen using the light stereomicroscope (OLYMPUS SZ II. Olympus optical Co. Tokyo, Japan) under x25 magnification to determine the location and type of failure whether it was cohesive or adhesive or mixed (fig 3 -6).…”
Section: Methodsmentioning
confidence: 99%